1996
DOI: 10.1097/00005537-199605000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral and Systemic Immunization on Nasopharyngeal Clearance of Nontypeable Haemophilus influenzae in BALB/c Mice

Abstract: BALB/c mice were immunized orally or subcutaneously with formalin-killed nontypeable Haemophilus influenzae (NTHi). Salivary immunoglobulin A (IgA) antibody titers against NTHi were significantly increased by oral immunization, but not by subcutaneous immunization. Both immunization procedures remarkably increased the levels of serum antibody activities of both IgA and immunoglobulin G. Live NTHi were then inoculated into the naso-pharynx, and the clearance of the pathogen from the nasopharynx was observed. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Several models have been useful in evaluating vaccine antigens for nontypeable H. influenzae. These include the chinchilla model of otitis media (21, 76, 114) and various pulmonary and nasopharyngeal clearance models in the mouse and rat (130,144,166,167,204,335,352). The ability of an antigen to generate a protective immune response in an animal model is used as a rationale to proceed with further testing of a potential vaccine antigen.…”
Section: Immune Response (I) Interpreting the Literature Human Antimentioning
confidence: 99%
“…Several models have been useful in evaluating vaccine antigens for nontypeable H. influenzae. These include the chinchilla model of otitis media (21, 76, 114) and various pulmonary and nasopharyngeal clearance models in the mouse and rat (130,144,166,167,204,335,352). The ability of an antigen to generate a protective immune response in an animal model is used as a rationale to proceed with further testing of a potential vaccine antigen.…”
Section: Immune Response (I) Interpreting the Literature Human Antimentioning
confidence: 99%
“…Enhanced clearance of NTHi from the middle ear was observed in chinchillas after systemic immunization with a mixture of outer membrane proteins, and the protection was associated with antigen-specific bactericidal antibodies (1,2,16). Enhanced NTHi clearance from the mucosal surface generally correlates well with antigen-specific mucosal IgA titer but not with serum IgA and IgG antibody levels after mucosal immunization (24). The present study showed that intranasal immunization with P6 and CT effectively enhanced the clearance of NTHi from the murine middle ear.…”
Section: Discussionmentioning
confidence: 47%
“…Suspensions were centrifuged, an aliquot from each supernatant was serially diluted 10-fold, and 10-l aliquots of the diluted samples were spread on chocolate agar plates to determine the concentration of live bacteria. After overnight incubation at 37°C in 5% CO 2 , NTHi was identified by standard bacteriologic techniques, including Gram staining and determination of their V and X growth factor requirements, and the colonies were counted (24). The concentration of NTHi was expressed as CFU per milliliter of ear wash.…”
Section: Methodsmentioning
confidence: 99%
“…These B cells are found in the tonsils and adenoids. Further support for the concept of a common mucosal immune system playing a role in the development of inflammation in the middle ear has been reported by Kurono et al [15] in Japan. Enhancement of mucosal IgA responses in the middle ear cavity against NTHi follows oral immunization with these bacteria [15].…”
Section: Lymphocyte Trafficking In the Middle Ear In Otitis Mediamentioning
confidence: 59%
“…Kurono et al [15] 1994 Both specific and nonspecific homing of lymphocytes from GALT and peripheral lymphoid tissue. Bernstein et al [14] 1988…”
Section: Investigatorsmentioning
confidence: 99%